Filipino Eden-tity framework formulation and shaping of a typical Filipino Middle-Class residential garden the case of Novaliches, Quezon City - Esposo, Jethro M. (College of Architecture, University of the Philippines Diliman, 2019)
Globalization and its negative effects has resulted to the nations lacking the sense of identity. Some key areas affected by globalization includes the landscapes and gardens as they were considered as symbols of national identity. The establishment of a nationally defined garden can greatly contribute to the development of a distinct national identity. Through time, well-established gardens have proven to boost a nation's identity through time, philosophy, tradition and cultural background of its people. These historical gardens are easily recognized through their tangible and intangible garden elements and display of their culture. Philippine as a developing country, with an absent architectural landscape identity should start developing its own. A Filipino garden that will represent and promote the identity of the Philippines. First, the study defines the 'Filipino'. Second, the study performs an on-site assessment of the Filipino gardens. Third, understanding the physical forms and symbolical meaning of the Filipino garden will be the study's findings. Lastly, a framework and a standardized Filipino garden should be well-presented in order to provide solution for the Philippines' identity.